Functional Calixarenes for Material and Life Science - Rodik, Roman; Cherenok, Sergiy; Kalchenko, Olga; Yesypenko, Oleksandr; Lipkowski, Janusz; Kalchenko, Vitaly (Current Organic Chemistry, 2018)
Calix[n]arenes – are easily accessible three-dimensional macrocyclic compounds. Modified calix[n]arenes capable with high selectivity recognize, bind in supramolecular complexes and separate substrates of similar properties such as cations, anions, gases, neutral organic molecules, and biomolecules. This review summarizes data on application as radionuclide extractants and sorbents, sensitive layer of chemosensors, porous materials for gases sorption, chromatography phases for (chiral) separation, stereoselective catalysts of organic reactions, resist for nanolithography, selective modulators of ATP-dependent pumps in smooth muscle cells, inhibitors of therapeutically important enzymes, vectors for gene transfection, fluorescent markers for cell imaging and “molecular glue” for protein crystallization of the functional calixarenes. Special attention in the paper is addressed to the application of the phosphorus-containing calixarenes in radiochemistry, chiral catalysis and bio-medicine.
Keywords: radionuclides